Adaptive thermogenesis in brown adipose tissue involves activation of pannexin-1 channels - Senthivinayagam, Subramanian (Mol Metab, 2020)
OBJECTIVE: Brown adipose tissue (BAT) is specialized in thermogenesis. The conversion of energy into heat in brown adipocytes proceeds via stimulation of β-adrenergic receptor (βAR)-dependent signaling and activation of mitochondrial uncoupling protein 1 (UCP1). We have previously demonstrated a functional role for pannexin-1 (Panx1) channels in white adipose tissue; however, it is not known whether Panx1 channels play a role in the regulation of brown adipocyte function. Here, we tested the hypothesis that Panx1 channels are involved in brown adipocyte activation and thermogenesis. METHODS: In an immortalized brown pre-adipocytes cell line, Panx1 currents were measured using patch-clamp electrophysiology. Flow cytometry was used for assessment of dye uptake and luminescence assays for adenosine triphosphate (ATP) release, and cellular temperature measurement was performed using a ratiometric fluorescence thermometer. We used RNA interference and expression plasmids to manipulate expression of wild-type and mutant Panx1. We used previously described adipocyte-specific Panx1 knockout mice (Panx1(Adip-/-)) and generated brown adipocyte-specific Panx1 knockout mice (Panx1(BAT-/-)) to study pharmacological or cold-induced thermogenesis. Glucose uptake into brown adipose tissue was quantified by positron emission tomography (PET) analysis of (18)F-fluorodeoxyglucose ((18)F-FDG) content. BAT temperature was measured using an implantable telemetric temperature probe. RESULTS: In brown adipocytes, Panx1 channel activity was induced either by apoptosis-dependent caspase activation or by β3AR stimulation via a novel mechanism that involves Gβγ subunit binding to Panx1. Inactivation of Panx1 channels in cultured brown adipocytes resulted in inhibition of β3AR-induced lipolysis, UCP-1 expression, and cellular thermogenesis. In mice, adiponectin-Cre-dependent genetic deletion of Panx1 in all adipose tissue depots resulted in defective β3AR agonist- or cold-induced thermogenesis in BAT and suppressed beigeing of white adipose tissue. UCP1-Cre-dependent Panx1 deletion specifically in brown adipocytes reduced the capacity for adaptive thermogenesis without affecting beigeing of white adipose tissue and aggravated diet-induced obesity and insulin resistance. CONCLUSIONS: These data demonstrate that Gβγ-dependent Panx1 channel activation is involved in β3AR-induced thermogenic regulation in brown adipocytes. Identification of Panx1 channels in BAT as novel thermo-regulatory elements downstream of β3AR activation may have therapeutic implications.